Lebar Bedengan untuk Genangan dalam Parit pada Tanaman Kedelai - Didik Indradewa; Soemartono Sastrowinoto; Supriyanto Notohadisuwarno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
saturated soil culture the width of the beds were recommended between I m and 2 m, which require more labor to dig the furrows. An experiment was done to study the effect of the width of beds and to determine the optimal bed's width. The experiment was done on Regosol soil in Sleman Regency, Yogyakarta using Randomized Complete Blocked Design with three blocks. The treatments were flood irrigation as control and saturated soil culture with I, 2, 3 and 4 m . wide of beds. Observations were done on soil moisture, physiological processes, growth and yield of soybean. The result of the experiment showed that saturated soil culture stabilized the soil moisture around field capacity, increased physiological processes, growth of the plant and increased the seed yield 81 %from 1.17 t ha-1 up to 2.12 t ha-l. There was no significant different on the effect of width of the beds, therefore 3-4 m bed's width was recommended. Keywords: Saturated soil culture, Soybean, Bed's width.